Acid hydrolysis reveals a low but constant level of pheomelanin in human black to brown hair. (9th December 2017) - Ito, Shosuke; Miyake, Shiho; Maruyama, Shoji; Suzuki, Itaru; Commo, Stéphane; Nakanishi, Yukiko; Wakamatsu, Kazumasa
Summary: We previously reported a constant ratio of the benzothiazole pheomelanin marker thiazole‐2, 4, 5‐tricarboxylic acid (TTCA) to the eumelanin marker pyrrole‐2, 3, 5‐tricarboxylic acid (PTCA) in eumelanic, black human hair. A constant level (20%–25%) of benzothiazole‐type pheomelanin was recently demonstrated in human skin with varying concentrations of melanin. Therefore, in this study, we aimed to investigate the origin of pheomelanin markers in black to brown human hair by developing a method to remove protein components from hair by heating with 6 M HCl at 110°C for 16 hr. For comparison, synthetic melanins were prepared by oxidizing mixtures of varying ratios of dopa and cysteine with tyrosinase. Hair melanins and synthetic melanins were subjected to acid hydrolysis followed by alkaline H2 O2 oxidation. The results show that the hydrolysis leads to decarboxylation of the 5, 6‐di‐hydroxyindole‐2‐carboxylic acid moiety in eumelanin and the benzothiazole moiety in pheomelanin and that eumelanic human hair contains 11%–17% benzothiazole‐type pheomelanin.